Genetic susceptibility for cow's milk allergy in Dutch children: the start of the allergic march?. Issue 1 (December 2015) - Henneman, Peter; Petrus, Nicole; Venema, Andrea; Sinderen, Femke; Lip, Karin; Hennekam, Raoul; Mannens, Marcel; Sprikkelman, Aline
Abstract Background Cow's milk allergy (CMA) is the most common allergic disease in infancy. It is not clear, whether infants with CMA have an increased risk of developing other allergic diseases later in life, the so-called "allergic march". We aimed to detect genetic associations of CMA using reported single nucleotide polymorphisms (SNP) in other allergic diseases and genetic mutations within the filaggrin (FLG ) gene. Both to investigate possible causes of CMA, which also suggests an "allergic march". Methods Thirty children from the Dutch EuroPrevall birth cohort study with CMA in infancy and twenty-three healthy controls were studied. Six candidate SNPs were selected (minor allele frequency 10–50 % combined with a large effect) based on the literature. ThirteenFLG candidate mutations were selected spread over repeats 1, 3, 4, 5, 6, 7, 9 and 10 respectively. Results We found two SNP's, rs17616434 (P = 0.002) and rs2069772 (P = 0.038), significantly associated with CMA. One is located near the toll like receptor 6 (TLR6) gene, which functionally interacts with toll-like receptor 2, and is associated with an increased risk of other allergic diseases. One is located at the Interleukin 2 (IL2 ) locus. TwelveFLG amplicons were analyzed, but showed no significant enrichment. Nevertheless, we did observe moreFLG mutations in the CMA-group compared to controls. Conclusion We significantly associated two SNPs with CMA, suggesting that variation in theTLR6 andIL2 genes contribute to the expression of CMA. In addition, sinceTLR6 andIL2 were earlier associated with other later onset allergies, this also favours the "allergic march" hypothesis. We observed moreFLG mutations in the CMA-group, albeit we found no statistical significant enrichment ofFLG mutations. Further studies are necessary to investigate the role of common variants andFLG or other skin barrier gene mutations in CMA.